BLENDED LEARNING A CONVERGENCE OF ONLINE LEARNING AND FACE-TO-FACE EDUCATION FOR IMPARTING BETTER EDUCATION IN INDIA - Kaur, Inderbir (PEOPLE: International Journal of Social Sciences, 2016)
Student sector in the developing world are frequently cited as being among the most important beneficiaries of online education initiatives such as massive open online courses (MOOCs). All over the world the concept of online learning is spreading at higher speed rather it is in junior education or in higher education. The convergence of online learning and face to face conversation to a different fold refers to a concept of Blended learning. Blended learning method refers to “mixing of different learning environments”. It combines traditional face-to-face classroom methods with more modern computer-supported activities using Internet and other advanced technology. According to History of Indian Education, Traditional teaching method is most popular method of teaching in Indian school which involves face to face interaction and cannot be eliminated from Indian education culture. Online learning, web based learning, intelligent tutor systems are the new technologies in education which helps in profound improvements. Online learning has unique abilities to provide students with enriched learning experiences, to extend learning beyond the school day, and to support more successful differentiated learning strategies that personalize students’ educational experiences. Web based learning has the advantage of learning through animations, multimedia, videos and chats etc. Blended learning is the teaching practice that combines teaching methods from both face-to-face and online learning and is going to prove as a powerful method of educational transfer.. So the objective of this paper is to explain how blended learning is essential in departing education. The paper not only describes the characteristics of blended learning but also put light on pillars of this learning scheme. Evidences are also there for the working of blended learning. Issues are also described for the need of blended learning in case of technical education in India which can be implemented with the concept of Massive Empowered Classrooms (MEC).